Operational Readiness Improvement in Make-to-Order Carton Packaging Systems: An Applied Industrial Engineering Study - Widyanti, Anggi Annastiti; Yitno Utomo; Manik Ayu Titisari (UNIPA PRESS, 2026)
Make-to-order manufacturing systems are highly dependent on operational readiness to ensure that available production time is effectively converted into output. In practice, many production facilities experience idle production days, where scheduled production time is available but no output is realized, leading to inefficiencies that are not fully captured by machine-based performance indicators alone. This study aims to analyze operational readiness in a carton packaging production system by examining the relationship between available production time, execution readiness, and output realization. A quantitative case study approach was applied using daily operational data from a carton packaging workshop, including planned production time, downtime, output records, and production execution status. The analysis differentiates between active production days and idle production days to identify readiness-related gaps affecting production utilization. The results show that high machine availability does not necessarily guarantee effective production execution, as a significant proportion of available production time remains unutilized due to readiness issues related to scheduling, material availability, and setup preparedness. This study provides applied insights into operational readiness improvement and offers practical recommendations to enhance production time utilization in make-to-order manufacturing environments. Key Words : applied industrial engineering; operational readiness; make-to-order manufacturing; production execution; carton packaging